Aerothermodynamic Analysis of Inflatable Aerodynamic Decelerators for CubeSats Reentry and Recovery - Cassineli - Palharini; Rodrigo (2023)
3 Specific objective 2: Analysis of the data obtained for non-reacting gas flows cases such as surface properties (heat flux, pressure, and skin friction coefficients) and flowfield structure (velocity, temperature, density, and pressure) around the vehicle. Publish the results in national and international conferences. TOTAL Despite very time-consuming simulations, it was possible to obtain all the results to complete this phase of the project and access the influence of inflatable aerodynamic decelerator geometry and reentry altitude on the surface properties and flow field structure. Due to the pandemic situation, it was not possible to participate at the all conferences planned early. However, the principal investigator of this project made an effort to publish the results at relevant conference virtually organized. All the results obtained in this phase can be found in the file "informeFinal111900" 4 Specific objective 3: Validation of the chemical reactions implemented into the dsmcFoam code. TOTAL Before conducting reactive gas flow over the IAD configuration at altitudes varying from 115 to 95 km altitude, this phase was dedicated to validate the set of chemical reactions implemented into the dsmcFoam code. The validation procedure was conducted using heat baths to test the reactions. Once each reaction was tested, numerical simulations of a reacting rarefied gas over a cylinder were conducted. The obtained results were compared with those found in the open literature and computed by mature DSMC codes as SMILE and MONACO. 5 Specific objective 4: Obtain the numerical solution for reacting flows over each inflatable aerodynamic decelerator configuration from 115 to 95 km altitude. PARCIAL At this phase, a new set of chemical reactions was implemented into the dsmcFoam+ code and validated using heat bath simulations and a reactive flow over the FIRE II vehicle. It was observed a good agreement between the reaction rates for the heat bath numerical experiment, where each reaction was tested separately. ...